ANALISIS PERBANDINGAN KINERJA KEUANGAN BANK SYARIAH DI INDONESIA, MALAYSIA, BRUNEI DAN THAILAND PERIODE 2011-2016 - Adyagunita Karini; Dian Filianti (Jurnal Ekonomi Syariah Teori dan Terapan, 2018)
Comparing the financial performance of banks with other countries would show if the different standards and regulations affect their performance. This research aims to know if there is a significant difference in financial performance of sharia banks between Indonesia, Malaysia, Brunei and Thailand during 2011-2016. The samples used in this research consist of one sharia bank from each country: Bank Syariah Mandiri, Maybank Islamic Berhad, Bank Islam Brunei Darussalam and Islamic Bank of Thailand. This research uses a comparative quantitativeapproach using Non Performing Financing (NPF), Financing to Deposit Ratio (FDR), Return on Asset (ROA), and Capital Adequacy Ratio (CAR) as variables to indicate financial performance. One-Way ANOVA is used as the analysis technique. Results of the ANOVA test show there is a significant difference in NPF, FDR, ROA and CAR between sharia banks in Indonesia, Malaysia, Brunei and Thaiand as indicated by a significance value of 0,000 and 0,002.  REFERENCESCarr, Marilyn dan Chen, Martha Alter. 2002. Globalization And The Informal Economy: How Global Trade and Investment Impact On The Working Poor. Working Paper on the Informal Economy 2002/1.Dahlan, M.Sopiyudin. 2008. Statistik untuk Kedokteran dan Kesehatan (Edisi 5). Jakarta: Salemba MedikaFahmi, Irham. 2012. Analisis Laporan Keuangan. Cetakan Ke-2. Bandung: Alfabeta.Ghozali, Imam. 2011. Aplikasi Analisis Multivariate Dengan Program IBM. SPSS 19. Semarang: Universitas DiponegoroHakim, Arif Rahman. 2017. Pengaruh Kondisi Ekonomi Makro dan Pross Manajemen Risiko Kredit terhadap Non-Performing Loan (Studi Kasus pada Bank X). Profit Jurnal Administrasi Bisnis Vol. 11, No. 2 2017.Haron, Sudin dan Yamirudeng, Majdi. 2003. Islamic Banking in Thailand: Prospects and Challenges. International Journal of Islamic Financial Services Vol.5 No.2. Ikatan  Akuntan  Indonesia,  2012. Standar Akuntansi  Keuangan.  PSAK.  Cetakan Keempat, Buku Satu, Jakarta: Penerbit Salemba Empat.Iriyanto, Guruh. 2016. Analisis Perbandingan Kinerja Keuangan Perbankan Syariah di Indonesia dan Malaysia Periode 2014. Naskah Publikasi. Universitas Muhammadiyah Surakarta.Rengaskamy, Dhanuskodi. 2014. Impact of Loan Deposit Ratio (LDR) on Profitability: Panel Evidence from Commercial Banks in Malaysia. Proceedings of the Third International Conference on Global Business, Economics, Finance and Social Sciences (GB14 Mumbai Conference) Mumbai, India. 19-21 December 2014Sugiyono. 2009. Metode Penelitian Bisnis (Pendekatan Kuantitatif, Kualitatif, dan R&D). Bandung: Alfabeta Sochih.  2008.  Analisis  Tingat  Kesehatan  Bank  Ditinjau  dari  Camel  (Capital, Asset  Quality,  Management,  Earning,  And Liquidity)  untuk  Mengukur Keberhasilan Manajemen pada Pt. Bprs Margirizki, Banguntapan, Bantul, Yogyakarta   (Studi   Kasus   Pada   Pt.   Bprs   Margirizki   Bahagia). Jurnal Pendidikan Akuntansi Indonesia Vol. Vi. No.2  -Tahun 2008:  82 –95The National Bureau of Asian Research. 2008. Islamic Finance in Southeast Asia; Local Practice, Global Impact. Seattle: The National Bureau of Asian Research Wibowo, Susanto. 2015. Analisis Perbandingan Kinerja Keuangan Perbankan Syariah dengan Metode CAMEL di ASEAN (Studi Komparatif: Indonesia, Malaysia, Thailand). Journal of Research in Economics and Management, Volume 15 No.1, Januari-Juni 2015: 136-153Widyaningsih, et all. 2005. Bank dan Asuransi Islam di Indonesia. Jakarta: KencanaYussof, Sheila Ainon. 2013. The Islamic Financial Services Act, 2013: Malaysia’s model framework for Shariah-compliance and stability. Islam and Civilisational Renewal (ICR),Vol. 4 No.3: 391-400